Food chemistry - Belitz, H.-D. [ (Hans-Dieter)]; Grosch, W. [ (Werner)]; Schieberle, Peter (Springer, 2009)
This book has long been the leading reference on food chemistry and technology. This latest edition covers new topics such as BSE detection, or acrylamide, and offers expanded treatment of food allergies and alcoholic drinks, or phytosterols